Light Nature Architecture - A Guide to Holistic Lighting Design (Prostor, 2024)
The phenomenon of light is deeply integrated into quotidian reality, but often not consciously perceived. In her book ‘Light Nature Architecture - A Guide to Holistic Lighting Design’, Ulrike Brandi presents authoritative discourse on the integration of natural light within architectural landscapes. By aligning theoretical insights with practical applications, her book emerges as a guide for architects, designers, and enthusiasts seeking an enlightened approach to lighting design.